PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) INDUSTRI RUMAH TANGGA (IRT) TEPUNG BUMBU KRISPI DI KELURAHAN KEDUNGKANDANG KOTA MALANG - Ratna Nikin Hardati Ratna Nikin Hardati; Imam Wahyudi Karimulloh; Ade Fitrianti; M. Rifqi Junaidi (Jurnal Abdi Insani, 2023)
Abstract : The role of a lecturer is very much needed, especially for the community around the university where the lecturer serves, one of the assistance needed is in terms of economic improvement, this is the background behind the Malang Islamic University to mobilize lecturers in its civitas environment to provide assistance to the community as a form of implementing the Tridharma college is dedication. In the context of this service, the devotees are targeting an UMKM IRT "Amanah" with Krispi Seasoning Flour, which is located in the Kedungkandang sub-district, Malang city. Referring to the results of the observation of needs, this service is aimed at improving the quality of production to make it more hygienic and economical, assistance in financial administration management also needs to be done to clarify the financial flow of production. The service method used is the mentoring method, namely giving a presentation of the material that has been prepared, which is then followed by discussion and training. The results of this service are able to improve the quality of production at "Amanah" IRT SMEs so that the quality of production becomes more hygienic, the addition of a new mixer machine makes the production process more economical and reduces production costs slightly, because it no longer requires human labor. Meanwhile, in relation to marketing, the use of new packaging is more attractive to consumers to choose "amanah" crispy seasoned flour products than other products, so that it is able to increase sales turnover in "Amanah" IRT MSMEs. The financial bookkeeping has been carried out according to mutually agreed procedures, so that it can increase trust between production members. With this assistance from the UNISMA Lecturer Service Team, of course, the "Amanah" IRT MSMEs are increasingly advanced, which also has an impact on increasing the welfare of the surrounding community, besides that many new knowledge is provided, one of which is good production governance and financial administration management in accordance with procedure.